ANALISIS PELUANG SINKRONISASI PROGRAM AMBULAN HEBAT SI CEPAT DALAM MENDUKUNG PELAKSANAAN PUSKESMAS MAMPU PONED DI PUSKESMAS BANGETAYU KOTA SEMARANG - Yuliastuti, Ika Kurnia; Jati, Sutopo Patria; Fatmasari, Eka Yunila (Jurnal Kesehatan Masyarakat (e-Journal), 2020)
Background : The city of Semarang is included in the top 5 highest maternal mortality rates in Central Java. The Semarang City Government through the Semarang City Health Service seeks to reduce maternal mortality through the establishment of community health centers capable of Basic Emergency Obstetric and Newborn Care (BEMONC) with the support of the establishment of the Ambulan Hebat program. Bangetayu Community Health Center is a community health centers capable of BEMONC that continues to contribute to maternal mortality in the last 3 years with the highest number of high risk pregnant women and the largest number of complications pregnant women. This study aims to analyze the opportunities for synchronizing the Ambulan Hebat program in supporting the implementation of community health centers capable of BEMONC at the Bangetayu Community Health Center.Method : Qualitative research with a descriptive analytic approach through in-depth interviews. The variables studied were elements of partnership (shared interests, openness & trust, clear & measurable goals, willingness to sacrifice, and mutual benefit) by using analysis of supporting factors and inhibiting factors (Force Field Analysis). Result : The results of this study indicate that the Ambulan Hebat Si Cepat program in supporting the implementation of obstetric and neonatal services in the Bangetayu Community Health Center based on the element of partnership has a great opportunity to synchronize. There are 4 elements of partnership that are supporting factors are the aspects of openness & trust, clear & measurable goals, willingness to sacrifice, and mutual benefit.Recomendation : The results of this study suggest that the Semarang City Health Office make policy regulations to regulate program coordination, conduct routine internal coordination, and create operational standards for special coordination procedures.